Comparison between a new thyroglobulin assay with the well‐established Beckman Access immunoassay: A preliminary report. Issue 2 (20th September 2020) - Cennamo, Michele; La Civita, Evelina; Curci, Anna; Liotti, Antonietta; Braschi, Umberto; Terracciano, Daniela
Abstract: Objectives: Measurement of serum thyroglobulin (Tg) plays a key role in the post‐thyroidectomy management of differentiated thyroid carcinoma (DTC). In this context, the performance of new‐generation thyroglobulin assay has clinical implications in the follow‐up of DTC patients. Aim of this study was to compare the new highly sensitive Liaison Tg II (Tg‐L) with the well‐established Tg Access assay (Tg‐A). Materials and methods: A total of 91 residual serum samples (23 positive and 68 negatives for Tg auto‐antibodies) were tested by the Beckman Access and Diasorin Liaison assays. Study samples were from 21 patients with pathologically proven DTC and control samples from 70 (16 patients with benign thyroid disease and 54 apparently healthy subjects). Results: Our results showed that Tg‐L was highly correlated with Tg‐A for both values ranging between 0.2 and 50 ng/mL (Pearson's r  = 0.933 [95%CI 0.894‐0.958], P  < .001) and higher than 50 ng/mL (Pearson's r  = 0.849 [95%CI 0.609‐0.946], P  < .001). For Tg values lower than 0.2 ng/mL, the overall concordance rate was 92%. Moreover, we tested 7 fine‐needle aspiration washout fluids (FNA), showing an overall concordance rate in discriminating negative and positive of 100%. Finally, we found no interference by Tg auto‐antibodies (TgAbs) for both Tg‐L and Tg‐A. Conversely, rheumatoid factor (RF) interferes with Tg‐A, but not with Tg‐L in one patient with no relapsing thyroid carcinoma. Conclusions: Liaison Tg II demonstrated a good correlation with Access Tg assay both for sera and FNAs. Further studies on larger population are needed to evaluate Tg‐L clinical impact on DTC patient's follow‐up.